2005
DOI: 10.1002/chem.200401008
|View full text |Cite
|
Sign up to set email alerts
|

Dichlororuthenium(IV) Complex of meso‐Tetrakis(2,6‐dichlorophenyl)porphyrin: Active and Robust Catalyst for Highly Selective Oxidation of Arenes, Unsaturated Steroids, and Electron‐Deficient Alkenes by Using 2,6‐Dichloropyridine N‐Oxide

Abstract: [Ru(IV)(2,6-Cl2tpp)Cl2], prepared in 90 % yield from the reaction of [Ru(VI)(2,6-Cl2tpp)O2] with Me3SiCl and structurally characterized by X-ray crystallography, is markedly superior to [Ru(IV)(tmp)Cl2], [Ru(IV)(ttp)Cl2], and [Ru(II)(por)(CO)] (por=2,6-Cl2tpp, F20-tpp, F28-tpp) as a catalyst for alkene epoxidation with 2,6-Cl2pyNO (2,6-Cl2tpp=meso-tetrakis(2,6-dichlorophenyl)porphyrinato dianion; tmp=meso-tetramesitylporphyrinato dianion; ttp=meso-tetrakis(p-tolyl)porphyrinato dianion; F20-tpp=meso-tetrakis(pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 161 publications
1
58
1
4
Order By: Relevance
“…Che and co-workers reported the Ru-porphyrin catalysed oxidation of ketosteroids to form diketosteroids using meso-tetrakis(2,6-dichlorophenyl)porphyrin (Ru(TDClPP)Cl 2 ) as catalyst and 2,6-Cl 2 pyNO as oxidant (Scheme 20) [82].…”
Section: Scheme 18 Oxidation Of Benzylic Alcohols To Carbonyl Compoumentioning
confidence: 99%
“…Che and co-workers reported the Ru-porphyrin catalysed oxidation of ketosteroids to form diketosteroids using meso-tetrakis(2,6-dichlorophenyl)porphyrin (Ru(TDClPP)Cl 2 ) as catalyst and 2,6-Cl 2 pyNO as oxidant (Scheme 20) [82].…”
Section: Scheme 18 Oxidation Of Benzylic Alcohols To Carbonyl Compoumentioning
confidence: 99%
“…These questions arise because halogenation of porphyrin ligands from tpp to 2,6-Cl 2 tpp and F 20 -tpp was found to increase the activities of ruthenium porphyrin oxidation catalysts, but 1 c was found to be a less effective catalyst than its F 20 -tpp analogue (1 b). [46] Moreover, although b-fluorination has been known to cause a large anodic shift in redox potentials of porphyrin rings, [20] few electrochemical studies have been reported on the change in redox potential of metal centers, especially in the case of oxometalloporphyrin complexes. To answer the questions, we examined the structures, spectral/electrochemical features, and reactivity of ruthenium porphyrin complexes bearing F 28 -tpp ligand (1 c, 2 c, and 3 c).…”
Section: Discussionmentioning
confidence: 99%
“…38 Lower b-selectivities as revealed by the b : a ratios of (7-26) : 1 were found for the epoxidation of 13a,b catalyzed by [Ru IV (2,6-Cl 2 tpp)Cl 2 ], with 14a,b obtained in 85-90% yields (substrate conversion: 100%). 38 The same catalytic system converted 13k to epoxide 14k in 89% yield with 99% substrate conversion. For the epoxidation of 13c to 14c, the reaction gave product turnovers of up to 1.6 Â 10 4 .…”
Section: Epoxidation Of Unsaturated Steroidsmentioning
confidence: 94%
“…40 A 99% yield of trans-4j, coupled with 99% substrate conversion, has been achieved for the oxidation of 3j by 2,6-Cl 2 pyNO using [Ru IV (2,6-Cl 2 tpp)Cl 2 ] as the catalyst. 38 The epoxidation of 3r with H 2 O 2 catalyzed by [Mn III (2,6-Cl 2 tpp)Cl] also gave 4r (80% yield) with a trans : cis ratio of 499 : 1. 40 Using the ''[Mn III (2,6-Cl 2 tpp)Cl] + H 2 O 2 '' oxidation system, a series of allyl-substituted cycloalkenes 3h-q,s-u have been epoxidized to 4h-q,s-u with moderate to high trans-selectivity, ranging from trans : cis ratios of (4-10) : 1 for 4h,i,p,u (52-83% yields) to trans : cis ratios of (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) : 1 for 4j,k,n,o,q,s,t (57-90% yields).…”
Section: Epoxidation Of Cycloalkenesmentioning
confidence: 95%